Alterations in Circulating MicroRNAs and the Relation of MicroRNAs to Maximal Oxygen Consumption and Intima–Media Thickness in Ultra-Marathon Runners - Eyileten, Ceren (Int J Environ Res Public Health, 2021)
The impact of long-term training on cardiovascular disease (CVD) is not clear. Carotid intima–media thickness (CIMT) test is recommended as a useful measure to diagnose the early stages of atherosclerosis. MicroRNAs (miRNAs) are altered due to endurance exercise and can be promising biomarkers of pathophysiological changes. We aimed to evaluate the association of circulating miRNAs with physical fitness and markers of atherosclerosis in ultra-marathon runners. Ultra-marathon runners had 28-fold upregulation of miR-125a-5p expressions compared to control individuals (p = 0.002), whereas let-7e and miR-126 did not differ statistically between ultra-marathon runners and controls. In the ultra-marathon runners’ group, negative correlations were observed between VO(2)max/kg and relative expression of miR-125a-5p and miR-126 (r = −0.402, p = 0.028; r = −0.438, p = 0.032, respectively). Positive correlations were observed between CIMT and miR-125a-5p and miR-126 (r = 0.388, p = 0.050; r = 0.504, p = 0.023, respectively) in ultra-marathon runners. Individuals with the highest quartile of VO(2)max/kg had 23-fold lower miR-126 expression in comparison to subgroups with lower VO(2)max/kg (p = 0.017). Our results may indicate that both miRNAs may serve as a biomarker for early pathological changes leading to atherosclerosis burden in athletes. Furthermore, the association between miRNAs and traditional risk factors for CVD indicate a possible use of these molecules as early biomarkers of future cardiovascular health.